Personal (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The following is an incomplete list of members and guests who. called at Institute headquarters during the period Dec. 10, 1917 to Jan. 10, , 1918: A. A. Arluck, Camp Merritt, N. J. W. Spencer Hutchinson, Boston, Mass. C. L. Bruns, Santiago de Cuba. William F. Jahn, New York, N. Y. Henry C. Carr, New York, N. Y. C. H. James, Tucson, Ariz. L. J. Charles, Santa Fe, N. M. Charles Janin, San Francisco, Cal. W. A. Deane, Waxhaw, N. C. Joseph T. Kupferstein, Shreveport, Pa. P. St. John Dixon, Rio de Janeiro, Brazil. Richard Lamb, New York, N. Y. M. C. Drake, Marquette, Mich. Walter R. Malm, San Francisco, Cal. F. W. Draper, Petrograd, Russia. W. H. Nash, Buffalo, N. Y. Paul W. Gaebelein, Boise, Idaho. Edmund Newton, Minneapolis, Minn. H. F. E. Gamm, Rutherford, N. J. Guy C. Riddell, Port Pirie, South Australia. C. A. Grabill, El Paso, Tex. Williams A. Simkins, San Francisco, Cal. William H. Hampton, New York, N. Y. Henry B. Smith, Northampton, Mass. R. M. Henderson, Brackenridge, Colo. H. E. Smith, Chicago, Ill. Geo. B. Holderer, Northpines, Ont., H: C. Spaulding, Washington, D. C. Canada. Y. Wakabayashi, Tokyo, Japan. H. H. Howry, Camp Upton. N. Y. A. P. Watt, Mine La Motte, Mo. L. Douglas Anderson", superintendent of the Midvale, Utah, smeltery of the United States Smelting Co., has been appointed manager of smelteries for the company at Salt Lake City, Utah.